The matrix recoded. - Ince, Darrell (Times Higher Education, 2010)
The article discusses information technology failures caused by human error and management problems. Based on reports of project failures from 2005-2010, the author highlights the recurring theme. He cites human error as the cause of the majority of major security incidents. He proposes modifying any software engineering course and human-computer interaction course to include material on project failure. He also recommends developing a new course on failure with a mix of technical, political, cultural and management topics.